Separation of Sb (V) and Sb (III) antimony compounds using anion exchange chromatography technique - Herlinawati Herlinawati; Buchari Buchari; M. Bachri Amran (Jurnal Pendidikan Kimia (JPKim), 2020)
Separation of Sb (V) and Sb (III) antimony compounds using anion exchange chromatography technique have been done. To obtain the separation of Sb (V) and Sb (III) antimony compounds which is good in this study have been studied several parameters of separation in anion exchange chromatography technique. Parameters that influence the process of separation of Sb (V) and Sb (III) antimony compounds is the concentration and pH of the mobile phase (eluent) have been evaluated. The separation of Sb (V) and Sb (III) antimony compounds is good and optimum obtained using an eluent 200 mM phosphate buffer at pH 7 with a flow rate of 1 mL/min. Based on the optimum conditions for the separation of Sb (V) and Sb (III) antimony compounds with anion exchange chromatography method has generated value the capacity factor (k ') Sb (V) and Sb (III) obtained are respectively 1.77 and 3.01. While the value of selectivity (α), Number of theoretical plates (N) and Resolution (Rs) obtained are respectively 1.70; 369.48; and 1.48.Keywords: Anion exchange chromatography, Capacity factor, Eluent, Resolution, Selectivity